Surviving the labor market: understanding the experiences of women and men with autism - Nagib, Wasan (My University, 2020)
People with Autism Spectrum Disorder (ASD) constitute the fastest-growing developmental disability population in North America, yet their employment outcomes are significantly poorer. Little attention has been given to the role of gender in shaping their employment experiences and the interface between their work and family demands. This qualitative research is intended to enable the ‘voice’ of people with autism to be heard through the content analysis of naturally occurring discourse in an on-line autism forum. The research is composed of three substantive studies. The first study investigated the role of gender in career exploration and job-seeking experiences. Guided by the Stages of Considering Work, the study examined how women and men with autism experienced three consecutive sets of vocational barriers related to contemplating employment, defining career goals, and finding jobs. The second study explored gender differences related to challenges in the workplace to maintain employment, including workplace mental health, social interaction, executive function, communication, disclosure, accommodation, sensory environment, and corporate cultures. The third study investigated the domestic experiences of women with autism as mothers, housekeepers, and caregivers, and how they negotiated the interface of work and family demands. Guided by the work/family border theory, the studyshowed how gender and disability identities significantly influenced their work-family experiences. Overall, this research informs gender-sensitive policies and practices to improve the employment and work-family balance experiences of individuals with autism.
Keywords: Autism; Gender; Workplace; Employment; Work-life balance